Corporate Marketing Referents to Green Consumer Intention: An Educated Young Malaysian Perspective (Journal of Governance and Development (JGD), 2012)
This study investigates marketing strategy affecting sustainable food consumption among the young educated population of a selected group at an excellent institute of training and information expertise in Malaysia. The investigation was based on pro environmental concerns / health consciousness, cost, convenience (availability) and communication (product info / labeling), as marketing references influence green consumption. Based on the planned behavior theory, these factors are considered as behavioral control elements to move towards a green attitude. A total of 174 participants from the academic members of University Utara Malaysia participated in this empirical research and findings of the study proved that consumers’ needs, cost, convenience and communication are influencing people’s intention to move towards green consumption.